Finding a Voice in Predominantly White Institutions: A Longitudinal Study of Black Women Faculty Members' Journeys toward Tenure. Issue 6 (June 2017) - Kelly, Bridget Turner; Winkle-Wagner, Rachelle
Background/Context: Amidst scholarship that underscores the importance of Black women faculty in higher education, Black women are often not being retained in faculty positions at research universities. There is a gap in the research relative to how Black women experience the tenure process at predominantly White institutions, and this may have important implications for both recruitment and retention of Black women faculty. Purpose: This analysis attempts to fill a gap in the literature on the recruitment and retention of faculty of color by asking: What are the experiences of Black women faculty on the tenure track at PWIs who are the only woman of color faculty member in their academic program? Drawing on data from qualitative longitudinal research with Black women faculty who were on the tenure track at PWIs, the primary purpose of this analysis was to understand four Black women's longitudinal reflections on their journey toward tenure at PWIs where they are "othered" by gender and race. Setting and Participants: This project was part of a larger study of 22 women faculty who were on tenure-lines in two predominantly White research universities. This study focused on four Black women from this larger study. Research Design: This study employed a qualitative longitudinal research design. Data Collection and Analysis: As part of the qualitative longitudinal research design, interviews were conducted each year for five years with each participant. Findings: The findings of this analysis with Black women faculty on the tenure-line suggests that despite being the only person of color in their academic programs, they found ways to use their voice in and outside the academy. Finding and using their voices in the academy became a way to push back and resist some of the isolation and racism that the women experienced in the academy, and often the women did so in collectivist spaces with other Black women. Conclusions/Recommendations: These findings of this study call into question predominantly White and male spaces in academia and ways that these spaces should be challenged to change. The Black women in this study coped by creating collectivist spaces and finding/ using their voices. Rather than focusing on how to encourage Black women to cope and survive in academia, there should be more emphasis on how to change institutional and departmental structures to make these spaces more inclusive and collectivist.